2020
DOI: 10.21203/rs.2.20140/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic polymorphism of the CYP2C19 gene in the Foshan area of Guangdong Province

Abstract: Background: The CYP2C19 gene is highly polymorphic, and CYP2C19 is involved in the broad interindividual variability of the clinical efficacy of certain clinical medications, such as clopidogrel. However, data on the CYP2C19 genotype in the Chinese population of the Foshan area of Guangdong Province are scarce. The purpose of this study was to determine CYP2C19 genetic polymorphisms in patients in the Foshan area and to compare the CYP2C19 genotype frequencies in different populations to determine the allele d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Hyperuricemia and gout, the most prevalent diseases in Guangdong province, were included. Our study showed that the prevalences of hyperuricemia and gout were 28.70 and 4.86%, respectively, which were higher than the pooled prevalences of gout in the adult population in China (13.3 and 1.1%, respectively) (38) and consistent with previous studies in Guangdong province (39). The main reasons for this phenomenon are closely related to the local characteristics of residents' eating habits.…”
Section: Figuresupporting
confidence: 90%
“…Hyperuricemia and gout, the most prevalent diseases in Guangdong province, were included. Our study showed that the prevalences of hyperuricemia and gout were 28.70 and 4.86%, respectively, which were higher than the pooled prevalences of gout in the adult population in China (13.3 and 1.1%, respectively) (38) and consistent with previous studies in Guangdong province (39). The main reasons for this phenomenon are closely related to the local characteristics of residents' eating habits.…”
Section: Figuresupporting
confidence: 90%